Deep neural network models for COVID-19 diagnosis from CT-Scan, explainability and analysis using trained models - Islam, Tahsin; Absar, Shahriar; Nasif, S.M. Ali Ijtihad; Mridul, Sadman Sakib (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.